Traumatic Death due to Simultaneous Double Spine Fractures in Patient with Ankylosing Spondylitis - Mitsuru Yagi; Shunsuke Sato; Atsushi Miyake; Takashi Asazuma (Case Reports in Orthopedics)
The aim of this study is to report the rare occurrence of simultaneous double spine fractures in a patient with progressive ankylosing spondylitis (AS). An 82-year-old male with established AS had low-energy falls. He had sustained simultaneous double spine fractures and died. Plain radiographs of the cervical spine were unremarkable in detecting a cervical spine fracture in a patient with AS and a spinal cord injury following a fall. CT scan showed a displaced fracture at the C6/C7 with American Spinal Injury Association-A spinal cord injury and displaced fracture at L1. The cause of death was determined to be upper spinal cord injury caused by cervical spinal fracture and dislocation that were facilitated by spinal rigidity from AS. This case report illustrates the importance of obtaining a detailed medical history and thorough imaging study when investigating deaths, including nonfatal conditions, such as AS. Furthermore, it shows the value of entire spine CT scan in the evaluation of the mechanism, further spine fractures, and manner of death. Despite the occurrence of spine fracture in AS patients, simultaneous double or multiple spine fractures are extremely rare and can be missed. Care should be taken for the further spine fracture in the entire spine in patient with AS.